Research on Lateral Control of Autonomous Driving for Autonomous-rail Rapid Tram - LIU Xiaocong; ZHOU Sheng; XIAO Lei; PENG Jing (Kongzhi Yu Xinxi Jishu)
To solve the problem of vehicle shaking and substantial lateral control deviation in the autonomous lateral control of autonomous-rail rapid tram and ensure its stable driving and safe lane changing on the road, this paper studies the road reconstruction process within the context of autonomous lateral control of autonomous-rail rapid tram. It proposes a road reconstruction method based on quadratic optimization, designs an autonomous tracking controller specifically tailored to autonomous-rail rapid tram, and establishes a dynamic model of autonomous-rail rapid trams for both simulation and verification on real vehicles. The experimental results show that during the transition phase of turning, the simulated path tracking deviation is ±4.8cm, while the real-vehicle experimental results show a deviation of ±5cm; under the high speed condition in straight road, the real-vehicle path tracking deviation is ± 0.2cm .These experimental findings underscore the satisfactory alignment between the theoretical vehicle model and the real vehicle. Furthermore, the autonomous driving process of the vehicle demonstrates the ability to effectively track the preset trajectory.